Issues in education. Early French immersion - Memorial University of Newfoundland. Educational Television Centre (Memorial University of Newfoundland. Educational Television Centre, 1980)
Aspects of early French immersion are discussed and observed in the primary education system. Thanks to teachers Nadine Carr, Francoise Bowring and the students of Holy Cross Primary School Minor distortion throughout.